Activities of the Wintering Party of the 35th Japanese Antarctic Research Expedition in 1994-1995 - Kotaro Yokoyama (Nankyoku shiryo, 1998)
The wintering party of the 35th Japanese Antarctic Research Expedition (JARE-35), which was consisted of 40 members, wintered at Syowa Station from February 1994 to January 1995. In the austral summer of 1993 to 1994,quite severe sea ice conditions forced the icebreaker SHIRASE to stop 20km from Syowa Station. The summer operations of transportation and construction were delayed and the wintering schedule had to be modified. However, the planned tasks were completed successfully. The main building of Syowa Station was completed after 3 years of construction improving living standards. The station facilities were maintained very well through the efforts of the logistic members. Observations at Syowa Station were conducted on various subjects such as meteorology, upper atmosphere physics and environmental sciences. The total ozone content reached a minimum value in October 1994. The incessant excitation of the Earth's free oscillations was confirmed by a superconducting gravimeter. Intensive field activities in geology, geomagnetism, marine biology and glaciology were carried out in the coastal areas, Yamato Mountains and inland plateau. The wintering period of JARE-35 was the 3rd year of the deep ice core drilling project at Dome Fuji Station. Several inland traverse parties were sent to the relay-point and Dome Fuji Station to transport fuel and construction materials. Nine members stayed at Dome Fuji Station for more than two months in the austral summer of 1994 to 1995 and completed the station for ice drilling. The newly arrived members of JARE-36 started wintering there, and by the end of JARE-37 wintering party's work an ice core over 2500m in depth was obtained.